Sistem Informasi Kontrol Dan Evaluasi Pemasaran Perumahan Pada Developer Properti Avenue Developments - Sofwan Agustria Al-Qodri, Ahmad; Br. Ginting, Novita; Eosina, Puspa (Jurnal Etnik: Ekonomi-Teknik, 2023)
Property developer Avenue Developments currently has 3 housing projects and will continue to develop in different locations. This certainly affects the process of controlling and evaluating marketing strategies, which will be increasingly difficult if done manually. Several obstacles were found related to the process of planning, implementing and reporting the results of marketing activities which could be detrimental to the company in terms of time, energy and costs spent on accommodation for the Marketing General Manager in holding meetings with the marketing team on each project. So an information system is needed to be able to process planning data, implementation data and reports on the results of marketing activities which can be accessed in real time by the General Manager, Sales Manager, Supervisor, Sales Admin and Sales. System development uses the Waterfall method, the system description will be described using the Unified Modeling Language (UML) modeling method. Data collection was carried out by directly observing the process of making action plans, implementation and evaluation of the results of marketing activities on each project as well as conducting interviews with related parties to analyze system requirements. The results of the research obtained an information system that can process data on planning, implementation and statistics on the results of marketing activities to facilitate the evaluation process by the Marketing General Manager.